CLASSROOM DISCOURSE ANALYSIS: AN ANALYSIS OF LECTURERS’ GESTURES TO ENGAGE THE STUDENTS. - Efendi, Ibnu Mirza; Puspitasari, Dewi; Rosyid, Ocid Abdul (Tomorrow's Education Journal, 2024)
Students’ engagement in the classroom is very important. It can increase the effectiveness of the learning process. What can be done to keep students engaged is to establish clear communication and support it with the right gestures. The aim of this research is to discuss and find out what gestures can be used to engage students. Meanwhile, the research method used is direct observation. Observations were carried out on three lecturers at the English Education Department, UIN KH. Abdurrahman Wahid, about what types of gestures are used in class and what the level of student engagement is from using these gestures. The results show that hand gestures, especially pointing, were carried out by the three lecturers and had quite a good impact on student engagement, especially students’ eye contact. However, the use of pointing is actually not used for just one function but for several functions. Such as showing material, selecting students, and so on. In conclusion, the use of gestures is very important for teachers. Apart from supporting verbal communication, this can increase students’ engagement in the classroom.